Traumatic Partial Aniridia and Cataract after Iris-Fixated Foldable Phakic Intraocular Lens Implantation - Joo Hyun; Jin Kwon Chung; Sung Jin Lee (Case Reports in Ophthalmology, 2013)
We present the first case of partial aniridia, traumatic cataract, and peripapillary subretinal hemorrhage after blunt trauma to an eye containing a foldable iris-fixated phakic intraocular lens (pIOL). Although the patient experienced visual loss because of considerable corneal astigmatism and a traumatic cataract, vision was recovered by a 2-stage primary corneal repair and cataract surgery with a toric intraocular lens. This case exhibits clinical manifestations that differ from previously reported trauma of a non-foldable iris-fixated pIOL. A relatively small corneal incision and a large optic diameter of Artiflex pIOLs may prevent posttraumatic total expulsion of intraocular tissues and present different clinical features from the case of non-foldable pIOLs (Artisan). Although the extent of the damage is different, the possibility of aniridia and traumatic cataract exists in eyes with both foldable and non-foldable iris-fixated pIOLs.